Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2012)
Ranibizumab and Bevacizumab for Treatment of Neovascular Age-related Macular Degeneration: Two – Year Results Comparison of Age – related Macular Degeneration Treatments Trials (CATT) Research Group Martin DF, Maguire MG, Fine SL, Ying G, Jaffe GJ, Grunwald JE, Toth C, Redford M, Ferris FL Ophthalmology 2012; 119: 1388-98. A Twenty-Year Follow-up Study ofTrabeculectomy: Risk Factors and Outcomes Landers J, Martin K, Sarkies N, Bourne R, Watson P, Ophthalmology 2012; 119, 694-702. Early Experience with the Femtosecond Laser for Cataract Surgery Bali SJ, Hodge C, Lawless M, Roberts TV, Sutton G, Ophthalmology 2012; 119: 891-9.